Banten’s Economic Growth: Regional Financial Performance Impacts (2014 – 2023) - Rahmatu Azzahra; Nugraha (IECON: International Economics and Business Conference, 2025)
This study investigates the role of local government policies in managing local finances towards economic growth in Banten Province in 2014 - 2023. This study aims to evaluate the level of fiscal decentralization, regional independence, and the effectiveness of local revenue in driving economic growth as measured by the growth of gross regional domestic product value. Quantitative research methods through causal descriptive are used to examine 80 observational data. The results show that fiscal decentralization has a negative effect on economic growth, while the level of regional independence and the effectiveness of local revenue have a positive effect on economic growth. The findings show that the implementation of local government policies in accordance with the principle of decentralization is very important in optimizing regional potential which ultimately has an impact on sustainable regional economic policies. This study highlights government policies in determining local revenue targets, increasing efficiency in regional development and governance, and allocation of accountable and transparent resources can encourage community welfare and regional development. The recommendations provided aim to evaluate policies and encourage innovation in the context of regional development through targeted fiscal policies.